Integrating indigenous aesthetic knowledge in upcycling used wood furniture - Md Ishak, Siti Mastura; Azmi, Nurin Adlina; Abdul Ghafar, Maszura; R. A. Effendi, Raja Ahmad Azmeer; Ibrahim, Roziya (Malaysian Consumer and Family Economics Association, 2024)
Tacit knowledge, as personal and experience-based expertise, plays a crucial role in upcycling used wood products (UWP), as it encompasses the intuitive skills and craftsmanship that Indigenous practitioners use to redesign and repurpose materials creatively. This study examines Indigenous experiences and tacit knowledge in upcycling used wood products (UWP), focusing on critical aspects like development time, craftsmanship expertise, and value appraisal. The research aims to analyze how Indigenous knowledge and experiences can contribute to evaluating and enhancing the upcycling process for UWP. This study addresses a critical gap in the upcycling process by focusing on the often-overlooked tacit knowledge inherent in community-centric upcycling, highlighting the potential of these practices to transform used UWP. This research contributes to sustainable practices and offers a model for incorporating Indigenous expertise into upcycling frameworks. The findings offer potential guidelines for professionals and small makers to integrate Indigenous knowledge and experiences into effective upcycling. Professionals can refine their understanding of the upcycling process and elevate the aesthetic experience of their products. At the same time, small makers can apply these insights to craft distinctive, sustainable designs that stand out. Future research could develop standardized guidelines for integrating Indigenous tacit knowledge into upcycling processes and examine the long-term impact of community-based upcycling on local economies and environmental sustainability.